2021
DOI: 10.1186/s13104-021-05492-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial survival on inanimate surfaces: a field study

Abstract: Objective Environmental surfaces may serve as potential reservoirs for nosocomial pathogens and facilitate transmissions via contact depending on its tenacity. This study provides data on survival kinetics of the most important nosocomial bacteria on a panel of commonly used surfaces. Type strains of S. aureus, K. pneumoniae, P. aeruginosa, A. baumannii, S. marcescens, E. faecium, E. coli, and E. cloacae were suspended in 0.9% NaCl solution at a McFarland of 1 and got then plated via cotton swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 53 publications
2
30
0
6
Order By: Relevance
“…The survival rate at 22 °C ( Figure 1 ) was observed to be strain specific, with a decreasing viability rate as time elapsed, and possible resources being consumed. In tested conditions (with 35% humidity), Staphylococcus aureus strains maintain high rates of viability, results that correlate with other literature reports [ 38 , 39 ]. R. H. Katzenberger et al (2021) observed the impact of high humidity in correlation with increased viability, especially on S. aureus strains.…”
Section: Resultssupporting
confidence: 90%
“…The survival rate at 22 °C ( Figure 1 ) was observed to be strain specific, with a decreasing viability rate as time elapsed, and possible resources being consumed. In tested conditions (with 35% humidity), Staphylococcus aureus strains maintain high rates of viability, results that correlate with other literature reports [ 38 , 39 ]. R. H. Katzenberger et al (2021) observed the impact of high humidity in correlation with increased viability, especially on S. aureus strains.…”
Section: Resultssupporting
confidence: 90%
“…Overall, this study provides important insights for fomite transmission and healthy building design for several reasons. Extensive studies have shown that pathogenic bacteria and fungi can persist on inanimate surfaces for prolonged period of time, leading to disease transmission 30,[60][61][62] . Especially in healthcare settings, numerous healthcare-associated infections and outbreaks have been associated with patient's care items, ranging from personal items such as computer keyboard and tablets, to common high touch surfaces such as curtain, window, hand sanitizers dispensers, and medical devices such as, medical chart and thermometers 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Especially in healthcare settings, numerous healthcare-associated infections and outbreaks have been associated with patient's care items, ranging from personal items such as computer keyboard and tablets, to common high touch surfaces such as curtain, window, hand sanitizers dispensers, and medical devices such as, medical chart and thermometers 33 . The three tested materials (plastic for PS, PVC fabric for textile, and glass) in this study are frequently used in building materials, furnishings and devices, which could serve as a reservoir for indoor pathogen that causes nosocomial infections 63 . Moreover, the selected bacteria and fungi are all pathogenic species that are known to cause nosocomial infections, with the exception of S. chartarum which are known to produce various mycotoxins and often related to Sick Building Syndrome 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Katzenberger et al described the percentage share of bacteria which play the main roles in outbreak events in hospitals, e.g., S. aureus (11.9%), K. pneumoniae (7.9%), P. aeruginosa (7.1%), A. baumannii (7.0%), S. marcescens (4.6%), E. faecium (3.6%), E. coli (2.4%) and E. cloacae (2.3%) [70]. According to Kramer et al, single-handed contact with a contaminated surface will have a variable degree of transmission depending on the bacteria.…”
Section: Bacteriamentioning
confidence: 99%
“…The longevity of bacteria increases the risk of spreading them in the hospital environment, especially in the conditions that exist in routine care of patients [72]. According to Katzenberger et al, 2021, the most susceptible bacteria to spread in the hospital environment are strains that are resistant to antibiotics, because they can more easily form biofilms on various surfaces, which may increase the likelihood of prolonged life and facilitate further spread [70].…”
Section: Bacteriamentioning
confidence: 99%